2006
DOI: 10.1128/iai.00895-06
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-Binding Protein 1a Promotes Resistance of Group B Streptococcus to Antimicrobial Peptides

Abstract: Evasion of host immune defenses is critical for the progression of invasive infections caused by the leading neonatal pathogen, group B streptococcus (GBS). Upon characterizing the factors required for virulence in a neonatal rat sepsis model, we found that a surface-associated penicillin-binding protein (PBP1a), encoded by ponA, played an essential role in resistance of GBS to phagocytic clearance. In order to elucidate how PBP1a promotes resistance to innate immunity, we compared the susceptibility of wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 69 publications
(72 reference statements)
0
45
1
1
Order By: Relevance
“…Penicillin-binding protein 1A mediates bacterial membrane stability and has been shown to promote resistance to antimicrobial peptides in Streptococcal species (147). Our observation suggests that penicillin-binding protein 1A may provide resistance against the host cathelicidin (15kDa protein A-like) observed during AOM.…”
Section: Discussionmentioning
confidence: 69%
“…Penicillin-binding protein 1A mediates bacterial membrane stability and has been shown to promote resistance to antimicrobial peptides in Streptococcal species (147). Our observation suggests that penicillin-binding protein 1A may provide resistance against the host cathelicidin (15kDa protein A-like) observed during AOM.…”
Section: Discussionmentioning
confidence: 69%
“…Both strains, for example, had »2-fold upregulation of ponA, which encodes the penicillin-binding protein 1a that was linked to phagosomal stress resistance in a prior study by protecting GBS against cationic antimicrobial peptides. 26 The cyl operon, which includes cylE, produces a pore-forming b-hemolysin/cytolysin (bH/C) and a carotenoid pigment that helps protect against reactive oxygen species. A previous study showed that a cylE deletion mutant does not produce either the bH/C or pigment and is more susceptible to both oxidative and macrophage killing.…”
Section: Cps Type Percent Survivalmentioning
confidence: 99%
“…Microorganisms have also developed ways to escape direct killing by human host defense peptides (171)(172)(173)(174), which emphasizes their important and ancient role in the innate immune system (172). However, resistance mechanisms are generally related to the direct killing of bacteria and are not comparable to the resistance mechanisms of conventional antibiotics.…”
Section: From Bench To Bedsidementioning
confidence: 99%